Technetium glucose complexes as potential cancer imaging agents. Issue 19 (1st October 2015) - Dapueto, Rosina; Aguiar, Rodrigo B.; Moreno, María; Machado, Camila M.L.; Marques, Fabio L.N.; Gambini, Juan P.; Chammas, Roger; Cabral, Pablo; Porcal, Williams
Graphical abstract: Abstract: GLUT's (facilitative glucose transporters) over-expression in tumor cells has allowed the detection of several cancer types, using a glucose analogue ( 18 F-FDG) with PET images, worldwide. New glucose analogs radiolabeled with 99m Tc could be a less-expensive and more accessible alternative for diagnosis using SPECT imaging.d -Glucose ( 99m Tc-IDAG) and 2-d -deoxyglucose ( 99m Tc-AADG) organometallic complexes were proposed and studied as potential 18 F-FDG surrogates. The glucose complexes were prepared and evaluated as potential cancer imaging agents, in a melanoma tumor model. Iminodiacetic acid (IDA) and aminoacetate (AA) moieties were chosen as chelating system for radiolabeling with 99m Tc. Tumor uptake of the formed complexes was evaluated in B16 murine cell line in vitro and in vivo in melanoma bearing C57BL/6 mice. In vitro and in vivo studies were conducted with 18 F-FDG in order to compare the uptake of 99m Tc-glucose complexes in the tumor model. IDAG and AADG compounds were synthesized and radiolabeled with 99m TcO4 − to obtain the 99m Tc-IDAG and 99m Tc-AADG complexes in high yield and stability. In vitro cell studies showed maximum uptake at 60 min for complexes, 99m Tc-IDAG and 99m Tc-AADG, with 6% and 2%, respectively. Biodistribution studies showed high tumor uptake one hour post-injection, reaching tumor-to-muscle ratios of 12.1 ± 3.73 and 2.88 ± 1.40 for 99m Tc-IDAG and 99m Tc-AADG, respectively. SPECT and micro-SPECT-CT images acquired after the injection of 99m Tc-IDAG showed accumulation in tumor sites, suggesting that this glucose complex would be a promising candidate for cancer imaging.